Mobilidade espacial para estudo e mudanças no espaço de vida dos estudantes de ensino superior da Região Norte Fluminense - Tavares, Jéssica Monteiro da Silva (2022)
The spatial mobility of the population has great relevance in urban spaces and in the dynamics of cities. Among the types of mobility, migration and commuting stand out. Despite the predominance of movements for work reasons, population displacements for study purposes are also relevant and deserve to be investigated. In this sense, the general objective is to analyze how spatial mobility transforms or causes changes in the set of places that the student experiences and in his own experience, in the light of the concept of living space. It is the search to enrich the study of population mobility, which results in changes in the living space of individuals. From the creation of typologies and mapping of the life space of students who move through space, the thesis intends to contribute with theoretical and methodological efforts to understand the phenomenon and its reflexes in individuals and in space, privileging the individual over the flow. Since the geography of opportunities varies from one region to another and spatial mobility is relevant in the composition of individuals' living space, based on the spatial relationships developed daily, a quantitative-qualitative approach is proposed in the analysis of population displacements for study in non-metropolitan areas, analyzing which causes, actors, implications and meanings build spatial mobility for study. In addition to the secondary data, a primary survey was carried out with an online questionnaire, due to the restrictions imposed by the pandemic, addressed to undergraduate students in the municipality. Subsequently, some profiles were selected to participate in the second phase, where the description, mapping and analysis of their living spaces were carried out. The results were presented through graphs, tables and maps. The profile of most participants is as follows: women (63.6%), with a predominance of the 20 to 24 years old group (55%), white (55%), single and without children (77%), with monthly family income of more than one to three minimum wages (45.5%), coming from public schools in basic education (70%). Most parents do not have completed higher education. The secondary residence is used by 20% of the participants, most of which are rented, contributing to the municipality's economy. The main reason for moving between primary and secondary residence is the study for 75% of the participants. The main places frequented by students in Campos were identified and, for the specific group of the second stage, the mapping of the individual living space was carried out, which reflected how each living space is configured according to spatial relationships and current and daily experiences of individuals, with their particular, circumstantial and experiential aspects. Given the objective and subjective conditions of available opportunities, spatial mobility can be activated as one of the strategies adopted to access these opportunities. In addition, it was possible to observe mobility as a life project of students, involving the desire to return to the place of origin or a continuation of the mobility situation in the future. In other words, in addition to individual issues, conjunctural aspects must also be taken into account, since the Geography of Opportunities is highly relevant for access to higher education.